Assertiveness and Behavior Analysis: a systematic review (Brazilian Journal of Behavioral and Cognitive Therapy, 2020)
This study aimed to identify and systematize published articles on the subject of Assertiveness and Behavior Analysis between 1998 and 2018. The following databases were consulted: OneFile; Scopus; Pubmed; Web of Science; Scielo; PePsic; PsycINFO and Google Scholar using the descriptors: 'assertiveness', 'Behavior Analysis' and 'assertive behavior' in Portuguese and English. Thirty articles were retrieved. The results indicated that most of the articles were published in Brazil, with a concentration of publications in the years 2011 and 2014. Most of the articles were of theoretical and correlational researches and, although the descriptor “behavior analysis” is used during searches, only six articles were based on the principles of Behavior Analysis. This article discusses the designs used, the use of inventories and implications for research, and the use of games as a form of intervention to teach assertive behavior.
Keywords: assertiveness; assertive behavior; behavioral analysis; social skills; systematic review